STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM PENGELOLAAN SUMBER DAYA MANUSIA UNTUK MENINGKATKAN MUTU PENDIDIKAN DI TARBIYATUL ATHFAL AL FARUQ KARANGLEWAS - Ismawati; Muh. Hanif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The goal of this research is to outline and evaluate the principal's human resource management tactics in order to raise the standard of instruction at Tarbiyatul Athfal Al Faruq Karanglewas. Using a qualitative case study methodology, information was gathered via in-depth interviews, documentation, and parent, teacher, and principal participation in observations. The results show that the principle serves as a strategic partner, mentor, and instructional manager in addition to being an administrator. Key strategies include strategic Human Resources planning, selective recruitment, regular training, supervision, and staff empowerment through open communication and performance appreciation. A culture of quality is cultivated through programs emphasizing spiritual values, discipline, and literacy, such as Qur’anic recitation (tasmi’), Islamic studies, and communal activities like morning assemblies and group prayers. Parents are actively engaged as part of the educational ecosystem through responsive communication and character-based programs. This participatory approach fosters a conducive and synergistic learning environment. The study concludes that transformative leadership, which integrates continuous improvement (Kaizen), collective participation, and a collaborative work culture, significantly enhances the quality of early childhood education. The findings imply that PAUD principals must be equipped not only with administrative competence but also with visionary leadership that empowers all stakeholders (including teachers, staff, and parents) to collaboratively build a sustainable culture of quality.